Luis Kutner and the development of the advance directive (living will) - Benzenhöfer, Udo; Hack-Molitor, Gisela (2009)
It is well known that Luis Kutner (1908-1993) played an important role in the development of the living will (advance directive, Patientenverfügung). But it is not clear when he developed his concept. We have screened the Luis Kutner Papers,deposited at the Hoover Institution Archives at Stanford University to answer this question. We found out that in the second half of 1967, Kutner dealt intensively with the issue of euthanasia. On December 7, 1967, he delivered a speech at the annual meeting of the Euthanasia Society in New York and presented the concept of the living will to the audience. So Kutner surely was a pioneer in this field, but further research is necessary to clarify, if he (or maybe Elsa W. Simon or Abraham L. Wolbarst) was the "originator" of the living will concept in the sense of passive euthanasia.